PENGARUH INTENSITAS PENGGUNAAN GADGET TERHADAP KONSEP DIRI - Rosalina, Lutfah; Budiono, Arifin Nur; Wahyuni, Wahyuni (FKIP Universitas Islam Jember, 2019)
This research was conducted to find out the extent of the influence of the intensity of the use of gadgets on the self-concept of class XI SMA Plus Al-Hasan Panti. The research method used is quantitative method and simple correlation. The participants were taken randomly using simple random sampling. This research was conducted by distributing a questionnaire to a predetermined sample. Based on the statistical test using the Pearson product-moment test, the r-value was 0.317 compared to the r table, the results obtained were 0.213. Further, the t-value was 3,064 compared to the t table, the results were 1,989, which means Ha was accepted and HO was rejected. Therefore, the gadget has a positive correlation with the students’ self-concept. Keywords: gadgets, self concept